1998
DOI: 10.1007/s004250050269
|View full text |Cite
|
Sign up to set email alerts
|

High levels of antioxidant enzymes correlate with delayed senescence in nonnetted muskmelon fruits

Abstract: We investigated the senescence process in two nonnetted muskmelon (Cucumis melo L.) varieties Clipper and Jerac diering in their storage life. Our results indicate that senescence in Jerac (the short-storage-life variety, less than 7 d) is the result of lipid peroxidation by free radicals, membrane phospholipid breakdown, and a drop in the level of antioxidants, resulting in increased membrane leakiness. By contrast, evidence is presented that the high levels of two enzymes implicated in antioxidative defence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 28 publications
8
114
0
2
Order By: Relevance
“…These results are in accordance with previous studies on S. lycopersicum (Cervilla et al, 2007), Malus domestica rootstocks (Molassiotis et al, 2006), and Vitis vinifera (Gunes et al, 2006). Moreover, the increase in LOX activity due to salt stress and B toxicity confirms higher lipolytic activity of the membrane and oxidation of membrane-bound fatty acids, which intensify peroxidation of lipids (Lacan and Baccou, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with previous studies on S. lycopersicum (Cervilla et al, 2007), Malus domestica rootstocks (Molassiotis et al, 2006), and Vitis vinifera (Gunes et al, 2006). Moreover, the increase in LOX activity due to salt stress and B toxicity confirms higher lipolytic activity of the membrane and oxidation of membrane-bound fatty acids, which intensify peroxidation of lipids (Lacan and Baccou, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…As stated by Lacan and Baccou (1998) when studying melon varieties, those fruit with higher antioxidant levels were able to be stored for longer periods, representing an extension in shelflife. However, Menichini et al (2009) reported that quality and quantity of such bioactive compounds are directly influenced by harvest stage, genotype, climate and cultivation techniques.…”
Section: Introductionmentioning
confidence: 91%
“…So, ripe or over-ripe fruit show an imbalance between reactive oxygen species production and scavenging mechanisms, which leads to cell death. Besides natural senescence, stressful conditions such as storage under chilling temperatures also lead to accumulation of peroxidation products [8].…”
Section: Antioxidant Enzymes and Lipid Peroxidation Analysismentioning
confidence: 99%
“…The oxidative stress is imposed as reactive oxygen species, superoxide ( ) and hydrogen peroxide (H 2 O 2 ) accumulate, resulting in metabolic disorder due to protein and nucleic acid oxidation and lipid peroxidation, which may be used as a maturity or stress indicator [5]. Therefore, whole or processed plant tissue with high antioxidant capacity presents a greater potential for tolerance to abiotic stresses such as cold [6,7] and extension of postharvest storage life [8].…”
Section: Introductionmentioning
confidence: 99%